The Effects of Varying Concentrations of Dietary Protein and Fat on Blood Gas, Hematologic Serum Chemistry, and Body Temperature Before and After Exercise in Labrador Retrievers - Ober, John; Gillette, Robert L.; Angle, Thomas Craig; Haney, Pamela; Fletcher, Daniel J.; Wakshlag, Joseph J. (Frontiers in Veterinary Science, 2016)
Optimal dietary protocols for the athletic canine are often defined by requirements for endurance athletes, that do not always translate into optimal dietary interventions for all canine athletes. Prior research studying detection dogs suggests that dietary fat sources can influence olfaction; however, as fat is added to the diet the protein calories can be diminished potentially resulting in decreased red blood cell counts or albumin status. Optimal macronutrient profile for detection dogs may be different considering the unique work they engage in. To study a calorically high protein: low fat (18:57% ME), high protein: high fat (27:57% ME), and high protein: low fat (27:32% ME) approach to feeding, 17 dogs were provided various diets in a 3 x 3 cross over design. Dogs were exercised on a treadmill and blood was taken pre-exercise, immediately post-exercise, 10 minutes and 20 minutes post-exercise to assess complete blood count, serum chemistry, blood gases, and cortisol; as well as rectal and core body temperature. Exercise induced a decrease in serum phosphorus, potassium, and increases in non-esterified fatty acids and cortisol typical of moderate exercise bouts. A complete and balanced high protein: high fat diet (27:57% ME) induced decreases in serum cortisol and alkaline phosphatase. Corn oil top dressed low protein: high fat diet (18:57% ME) induced a slightly better thermal recovery than a complete and balanced high fat: high protein diet and a low fat: high protein (32:27% ME) diet suggesting some mild advantages when using the high fat: low protein diet that warrant further investigation regarding optimal protein and fat calories and thermal recovery.